IDENTIFIKASI BAHAYA DAN PENILAIAN RISIKOKESELAMATAN DAN KESEHATAN KERJA PADA AREA PRODUKSI PT X TAHUN 2023 - Seila Delfina Harianja (2023)
PT X is a lubricant manufacturing industry that has work processes with high hazards and risks. Several cases of work accidents that have occurred are thought to have prevented or reduced their impact by carrying out hazard identification and risk assessment activities which had not been updated at the time of the research.This study was conducted to hazard identification and risk assessment with HIRADC using qualitative research types. There were six informants with purposive sampling technical they consist of 2 workers, 3 supervisors and 1 Safety Environment. The results of the study found the hazard in Refinery Plant including physical and chemical hazards. In addition, the hazard in PPIC including physical, chemical and ergonomic hazards. The risks contained in both units still have a medium level of risk. Final risk assessment on each unit found Refinery Plant has 9 or 69% hazard with category risk low and 8 or 31% hazard with category risk medium. In PPIC found 5 or 24% medium and 16 or 76% low. Companies are advised to update their HIRADC assessment at least once a year.